Co-creation of value for cultural festivals: behind the scenes in Macau. Issue 4 (1st October 2020) - Chen, Zhaoyu; King, Brian; Suntikul, Wantanee
ABSTRACT: In their capacity as performative cultural assets located in destinations, festivals offer visitors potentially convivial and memorable experiences. Though previous studies have examined the psychologies of festival attendees, few have considered the perspective of festival stakeholders towards the co-creation of cultural value. The present study examines the case of a traditional festival that epitomises intangible cultural heritage – the Feast of Na Tcha in Macau. The researchers examine how organisers, performers, government officials, local shop owners and tourists play roles in co-creating value for the festival. The paper examines an overlooked dimension – contributions from multiple stakeholders to the multifaceted concept of value in cultural festival settings. The findings present a value co-creation paradigm that may inform prospective creative enhancements to the festival experience.